Why do we suffer more ACL injuries in the cold? A pilot study into potential risk factors. (January 2017) - Csapo, Robert; Folie, Ramona; Hosp, Simona; Hasler, Michael; Nachbauer, Werner
Abstract: Objectives: This study aimed to investigate temperature-related changes in different neuro-muscular parameters, to elucidate the reasons for the increased likeliness of injuries of the anterior cruciate ligament under cold environmental conditions. Design: Repeated measures study design. Methods: To induce peripheral cooling of the knee joint and thigh muscles, ten healthy, female subjects underwent 30 min of exposure to a cold environment. Both knee extensor and flexor muscles were examined for electromyographic activity, maximum voluntary contraction strength, rate of force development and force sense. Measures of knee laxity were obtained by computerized arthrometry. Results: Following cold exposure, rate of force development of the knee flexor muscles was significantly reduced ( p  = 0.016). Left-shifts of electromyography power spectra indicated changes in neural drive to the medial and lateral head of the vastus muscle. Maximum strength, force sense and knee laxity were not affected by the intervention. Conclusion: The reduced capacity of cold knee flexor muscles to explosively generate force may limit the hamstrings' capability to counter strong and fast contractions of the knee extensor muscles that cause anterior shear force on the tibia and, thus, strain the anterior cruciate ligament. Highlights: Cooling of thigh and knee changes the EMG frequency power spectrum of knee extensor muscles. The capacity to generate fore explosively is particularly reduced in knee flexor muscles. Knee laxity, force sense and maximum strength are not affected by cold exposure.